UJI EFEKTIVITAS EKSTRAK DAUN DUWET (Syzygium cumini (L.) Skeels) TERHADAP MORTALITAS LARVA Aedes aegypti - Ismia Agustini, (2019)
Dengue Hemorrhagic Fever (DHF) is an endemic disease in Indonesia with high mortality rates. Controlling the vector of DHF disease using Larvicide is one of the efforts that can be done in eleminating DHF disease. The harm that is caused by chemical larvicides leads to the need for natural larvicides as an alternative. Duwet's Leaf (Syzygium cumini (L.) skeel) becomes a potential natural larvicide because it contains active compounds in the form of flavonoids, tannins, alkaloids, saponins that can lead to the death of Aedes aegypti's larvae. This research used experimental design. The research samples used are larvae of A. aegypti stage III and IV which is given treatment using Duwet's leaf extract concentrations of 1.5%, 3%, 5%, and 7.5% with positive (abate) and negative control (aquades). Twenty five larvae were put into the glass and incubated for 24 hours, and the numbers of dead larvae were counted afterward. ANOVA's one-way test result (P = 0.000) indicates that there was a significant difference between a group of Duwet's leaf extracts to the mortality of A. aegypti larvae. Post Hoc (Bonferroni) test results show that there was a difference in effectiveness at each compared concentration. Based on the results of this study, the Duwet's leaf extract has the effectiveness of larvicides on A. egypti's larvae